Meta-analysis finds large variation but no general patterns in the relationship between climate and parasitism in terrestrial animals - Hannah S. Wolmuth-Gordon; Julia Koricheva; Mark J. F. Brown (Proceedings of the National Academy of Sciences, 2025)
Climate can vary spatially and temporally and is becoming increasingly unpredictable due to climate change. It can have a large impact on host–parasite interactions and investigating this effect is vital both for understanding current parasite distribution and epidemiology, and predicting how this will change in the future. Here, we conducted a meta-analysis to determine whether temperature and precipitation have an overall effect on parasite prevalence and infection intensity in terrestrial animals. This is a phylogenetically controlled quantitative synthesis to assess parasite prevalence and infection intensity in terrestrial animals across contrasting temperatures and precipitation. We found large variation in the effect of temperature on parasite prevalence, precipitation on parasite prevalence, and temperature on infection intensity. This provides robust quantitative evidence against the controversial “warmer sicker world” hypothesis. There was no effect of climate on parasitism, irrespective of whether the parasite was an endoparasite or ectoparasite, or across different parasite lifecycles. Although some host and parasite taxa were understudied, we found no consistent taxonomic patterns. Importantly, we revealed large gaps in the literature, including the relationship between humidity, prevalence, and infection intensity. Ectoparasites and reptile hosts were also very underrepresented, and deserve further study. Focusing future research on these gaps will help to confirm whether certain types of host–parasite interactions are more or less sensitive to changes in climate, with implications for conservation.